ISLAMIC RELIGION AND VALUES IN INDEPENDENT UZBEKISTAN - Azamova, Mukhabbat Ganijonovna (Educational Research in Universal Sciences, 2023)
This article mainly talks about the historical forms of religion, the unique features of our religion, the main ideas in it. Also, the issue of freedom of conscience in independent Uzbekistan will be touched upon.